Laser Vision Correction with Q Factor Modification for Keratoconus Management. (3rd April 2017) - Pahuja, Natasha Kishore; Shetty, Rohit; Sinha Roy, Abhijit; Thakkar, Maithil Mukesh; Jayadev, Chaitra; Nuijts, Rudy MMA; Nagaraja, Harsha
ABSTRACT: Purpose : To evaluate the outcomes of corneal laser ablation with Q factor modification for vision correction in patients with progressive keratoconus. Methods : In this prospective study, 50 eyes of 50 patients were divided into two groups based on Q factor (>−1 in Group I and ≤−1 in Group II). All patients underwent a detailed ophthalmic examination including uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), subjective acceptance and corneal topography using the Pentacam. The topolyzer was used to measure the corneal asphericity ( Q ). Ablation was performed based on the preoperative Q values and thinnest pachymetry to obtain a target of near normal Q . This was followed by corneal collagen crosslinking to stabilize the progression. Results : Statistically significant improvement ( p ≤ 0.05) was noticed in refractive, topographic, and Q values posttreatment in both groups. The improvement in higher-order aberrations and total aberrations were statistically significant in both groups; however, the spherical aberration showed statistically significant improvement only in Group II. Conclusion : Ablation based on the preoperative Q and pachymetry for a near normal postoperative Q value appears to be an effective method to improve the visual acuity and quality in patients with keratoconus.